Pengaruh Harga Promosi Dan Lokasi Terhadap Keputusan Pembelian Pada Gerai Indomaret Mandai Maros - Pawawoi, Andi Agung; Syam, Andi Hendra; Guntur, Ihsan (Movere Journal, 2024)
This research aims to analyze the influence of price, location and promotion on purchasing decisions. The data used in this research is primary data collected from the results of distributing questionnaires to 60 consumers at Indomaret Mandai Maros. With a sampling technique using the Convenience Sampling technique. The data processing method uses multiple linear regression methods. Findings the research is found that price has a significant effect on purchasing decisions, location has a significant effect on purchasing decisions, promotion has a significant effect on purchasing decisions. As well as simultaneous testing of all price, location and promotion variables have a significant effect on purchasing decisions. Keyword : Purchasing Decisions, Price, Place and Promotion